A Real World 10-Year Experience With Vascular Closure Devices and Large-Bore Access in Patients Undergoing Transfemoral Transcatheter Aortic Valve Implantation - Heitzinger, Gregor; Brunner, Christina; Koschatko, Sophia; Dannenberg, Varius; Mascherbauer, Katharina; Halavina, Kseniya; Doná, Carolina; Koschutnik, Matthias; Spinka, Georg; Nitsche, Christian; Mach, Markus; Andreas, Martin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Transcatheter aortic valve replacement (TAVR) has established itself as a safe and efficient treatment option in patients with severe aortic valve stenosis, regardless of the underlying surgical risk. Widespread adoption of transfemoral procedures led to more patients than ever being eligible for TAVR. This increase in procedural volumes has also stimulated the use of vascular closure devices (VCDs) for improved access site management. In a single-center examination, we investigated 871 patients that underwent transfemoral TAVR from 2010 to 2020 and assessed vascular complications according to the Valve Academic Research Consortium (VARC) III recommendations. Patients were grouped by the VCD and both, vascular closure success and need for intervention were analyzed. In case of a vascular complication, the type of intervention was investigated for all VCDs. The Proglide VCD was the most frequently used device (n= 670), followed by the Prostar device (n = 112). Patients were old (median age 83 years) and patients suffered from high comorbidity burden (60% coronary artery disease, 30% type II diabetes, 40% atrial fibrillation). The overall rate of major complications amounted to 4.6%, it was highest in the Prostar group (9.6%) and lowest in the Manta VCD group (1.1% p = 0.019). The most frequent vascular complications were bleeding and hematoma (n = 110, 13%). In case a complication occurred, 72% of patients did not need any further intervention other than manual compression or pressure bandages. The rate of surgical intervention after complication was highest in the Prostar group (n = 15, 29%, p = 0.001). Temporal trends in VCD usage highlight the rapid adoption of the Proglide system after introduction at our institution. In recent years VCD alternatives, utilizing other closure techniques, such as the Manta device emerged and increased vascular access site management options. This 10-year single-center experience demonstrates high success rates for all VCDs. Despite successful closure, a significant number of patients does experience minor vascular complications, in particular bleeding and hematoma. However, most complications do not require surgical or endovascular intervention. Temporal trends display a marked increase in TAVR procedures and highlight the need for more refined vascular access management strategies.